Genome-Wide Identification and Characterization of Receptor-Like Protein Kinase 1 (RPK1) Gene Family in Triticum aestivum Under Drought Stress - Rahim, Amna Abdul; Uzair, Muhammad; Rehman, Nazia; Rehman, Obaid Ur; Zahra, Nageen; Khan, Muhammad Ramzan (Frontiers in Genetics, 2022)
Receptor-like protein kinase1 (RPK1) genes play crucial roles in plant growth and development processes, root architecture, and abiotic stress regulation. A comprehensive study of the RPK1 gene family has not been reported in bread wheat (Triticum aestivum). Here, we reported the genome-wide identification, characterization, and expression patterns of the RPK1 gene family in wheat. Results confirmed 15 TaRPK1 genes, classified mainly into three sub-clades based on a phylogenetic tree. The TaRPK1 genes were mapped on chromosomes 1–3 in the respective A, B, and D genomes. Gene structure, motif conservation, collinearity prediction, and synteny analysis were carried out systematically. A Gene ontology study revealed that TaRPK1 genes play a vital role during molecular and biological processes. We also identified 18 putative miRNAs targeting TaRPK1 genes, suggesting their roles in growth, development, and stress responses. Cis-Regulatory elements interpreted the presence of light-related elements, hormone responsiveness, and abiotic stress-related motifs in the promoter regions. The SWISS_MODEL predicted the successful models of TaRPK1 proteins with at least 30% identity to the template, a widely accepted threshold for successful modeling. In silico expression analysis in different tissues and stages suggested that TaRPK1 genes exhibited the highest expression in root tissues. Moreover, qRT-PCR further validated the higher expression of TaRPK1 genes in roots of drought-tolerant varieties compared to the drought-susceptible variety. Collectively, the present study renders valuable information on the functioning of TaRPK1 genes in wheat that will be useful in further functional validation of these genes in future studies.